Fault tolerant control for spacecraft attitude control systems - Shen, Qiang (2016)
Future spacecraft are expected to achieve highly accurate pointing, fast slewing from large initial condition, and reliable maneuvers in the presence of environmental disturbances, unknown or uncertain inertia parameters, control input saturation, and component failures. Actuators play an important role of generating control torque/force in the desired direction under command from the controller to achieve specific aerospace objectives. However, an abrupt occurrence of an actuator fault/failure could significantly disrupt mission performance or even lead to totally loss of the spacecraft. In order to enhance the reliability and reduce critical failure of spacecraft, fault-tolerant capability should be addressed in the control system of spacecraft. Generally, the available fault-tolerant control (FTC) schemes can be classified into two categories: active FTC and passive FTC. In this thesis, both active and passive FTC approaches are developed for attitude control systems of spacecraft to enhance reliability and safety while achieving high precision attitude maneuver.